2020
DOI: 10.1017/s1368980020002463
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes among children treated for uncomplicated severe acute malnutrition: a retrospective study in Accra, Ghana

Abstract: Objectives: The objectives of the study were to describe outcomes of children with uncomplicated severe acute malnutrition (SAM) attending community-based management of acute malnutrition (CMAM) treatment centres in Accra Metropolitan Area (AMA) and explore factors associated with non-adherence to clinic visits and defaulting from the treatment programme. Design: A retrospective cohort study analysing routinely collected data on children with uncomplicated SAM enrolled into CMAM in 2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Primary and secondary outcomes. We enrolled 1,231 children (708 [58%] were female and 513 [42%] were male) with a median age of 14 months (IQR, [10][11][12][13][14][15][16][17][18][19]. Clinical data are reported in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary and secondary outcomes. We enrolled 1,231 children (708 [58%] were female and 513 [42%] were male) with a median age of 14 months (IQR, [10][11][12][13][14][15][16][17][18][19]. Clinical data are reported in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Takyi et al confirmed poor adherence to NRPs for children in Ghana and argued that greater efforts must be made to promote adherence. 12 A study performed in Ethiopia involving HIV-positive adult patients showed poor adherence to nutritional programs and that the only sociodemographic variable with a significant effect on adherence is the educational status. 13 Therefore, further studies are needed to evaluate the factors that negatively affect adherence to health programs for children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mid‐upper arm circumference (MUAC), a common anthropometric measurement, is being used especially in emergency and crisis settings to assess the nutritional status of children, which might be an alternative option to measure WLZ/WHZ (Briend et al, 1987 ; Sultana et al, 2015 ; World Health Organization (WHO) Working Group, 1986 ). Children with a MUAC of less than 11 cm are categorized as malnourished (Bari et al, 2019 ; Briend et al, 1987 ; Fernández et al, 2010 ; Hossain et al, 2017 ; Takyi et al, 2020 ). Literature suggested several cut‐off values for MUAC, which range from <11 to 12.5 cm (WHO, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiological studies focused on iodine (24,25) , anaemia (26,27) , linear growth (28) and obesity (29) . All three intervention studies deal with undernutrition (30)(31)(32) . The double burden of malnutrition and the 'double duty actions' (33) are not specifically addressed although the issue is discussed in the qualitative papers on community solutions.…”
mentioning
confidence: 99%